Decontamination Foam Containing Silica Nanoparticles of Various Structures - Yoon, In-Ho; Bon Yoon, Suk; Jung, Chong-Hun; Kim, Chorong; Yoon Park, Sang; Moon, Jei-Kwon; Choi, Wang-Kyu (Asian Journal of Chemistry, 2014)
The purpose of the present study is to investigate the silica nanoparticles of various structures for their foam stability and dissolution using decontamination foam. Silica nanoparticles of various structures such as mesoporous, core-shell and non-porous silica nanoparticles were synthesized for an evaluation of decontamination foam. Compared to foam stabilized with only 1 % ElotantTM Milcoside 440N (EM440N) surfactant, the addition of 1 wt. % mesoporous nanoparticles improves the foam stability by a factor of 8. The oxide dissolution was evaluated using decontamination foam with silica nanoparticles and 1 M HNO3 using corroded specimens. The mixture of mesoporous nanoparticles in the surfactant improves the oxide dissolution by a factor of 2 compared with the surfactant only. These results indicate that the mesoporous silica nanoparticles improve the foam stability and oxide dissolution owing to an enhancement in the contact time of the chemical reagent and the corroded specimen.